2022
DOI: 10.3389/fpsyg.2022.935254
|View full text |Cite
|
Sign up to set email alerts
|

Childhood adversity and cognitive impairment in later life

Abstract: ObjectivesThis study examined the association between childhood adversity and cognitive impairment in later life and explored the potential moderation effect of gender and race.MethodsThe study sample included 15,133 participants of the Health and Retirement Study (1998–2016 surveys) who had complete data on key study measures and were more than 50. The outcome variable is a dichotomous indicator of cognitive impairment as assessed by the Telephone Interview for Cognitive Status for self-respondents and the 16… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 64 publications
0
4
1
Order By: Relevance
“…Notably, the non-significant relationship between lifetime abuse victimization and memory was contrary to a prior, U.S.-representative study that showed the long-term effects of childhood abuse on cognitive impairment in later life (Xiang et al, 2022). There was a significant lagged effect of depression from the prior data collection on memory (See Supplementary Table 5).…”
Section: Discussioncontrasting
confidence: 99%
“…Notably, the non-significant relationship between lifetime abuse victimization and memory was contrary to a prior, U.S.-representative study that showed the long-term effects of childhood abuse on cognitive impairment in later life (Xiang et al, 2022). There was a significant lagged effect of depression from the prior data collection on memory (See Supplementary Table 5).…”
Section: Discussioncontrasting
confidence: 99%
“…But the magnitude of this association shown in this study was alarming. After correction for multiple comparison, childhood health and financial situation did not appear to be a significant risk factor for the comparatively worse trajectories, although previous literature has indicated the lifelong impact of childhood adversities on these three conditions in later life [ 63 – 65 ]. This could also be due to the observed strong association between participants’ self-rated health at baseline and the trajectories.…”
Section: Discussionmentioning
confidence: 81%
“…However, other work has shown that early life adversity, as measured by food deprivation and being thinner in childhood, was associated with a slower rate of cognitive decline in older African Americans 39 . Similarly, Xiang et al 40 found that parental substance abuse in childhood was associated with a lower risk of incident cognitive impairment in the Health and Retirement Study. Our findings suggest that resilience and posttraumatic growth may be possible mechanisms in this sample of caregivers 41 .…”
Section: Discussionmentioning
confidence: 95%